A Novel High Voltage Gain SEPIC Converter Based on Hybrid Split-Inductor for Renewable Application. Issue 5 (3rd September 2022) - Kumar, Dileep; Gupta, Ram Avtar; Tiwari, Harpal
ABSTRACT: The modified single-ended primary inductor converter (SEPIC) reported in the literature has limitations namely, low static gain and high input current ripples. This resulted in poor efficiency with high switching losses and switching stress. Hence, in order to overcome the above-said limitations, this paper proposes a high static gain SEPIC converter with reduced input current ripple. The proposed converter resembles a split-inductor design consisting of three diodes and two inductors. The static gain of the converter is significantly improved while input current ripple gets reduced by using a split-inductor. Additionally, the low value of input current ripple causes minimal switching stress and switching losses. Hence, the efficiency of the proposed converter improves significantly. The working principle and theoretical analysis of the proposed converter is studied in detail for continuous, discontinuous and boundary conduction modes. Moreover, a small signal/transient analysis is also discussed to validate the feasibility as well as the stability of the proposed system using the transfer function approach. In order to validate the effectiveness of the proposed converter, a MATLAB/Simulink model has been designed. Further, a laboratory prototype has been developed and the experimental results obtained are in agreement with the simulated results.